A house of kings : the official history of Westminster Abbey - Carpenter, Edward, 1910-1998 (New York : John Day Co., 1966)
From 1066 to 1966, with special studies on the architecture, coronations, music and sacristy of the Abbey
Keywords: History of Christianity (3JGQjN GdeSjMjIs; History